Indebida aplicación de la normativa que regula la prestación de alimentos a los obligados subsidiarios cuando estos adolecen de enfermedades catastróficas - Paucar Flores, Ana Katiushka (2023)
The Constitution of the Republic of Ecuador recognizes the primacy of children's and adolescents' rights, as well as the rights of persons who are afflicted with catastrophic diseases. According to the Code of Children and Adolescents, alimony must be paid to the subsidiary obligors without considering the situation of those suffering from catastrophic diseases. All children and persons with catastrophic diseases are entitled to free specialized care in all areas and at all levels, thus ensuring their rights and guarantees are protected. In Ecuador, the Childhood and Adolescence Code establishes food obligations in favor of children and adolescents, and names subsidiary obligors in case parents fail to meet the obligation. However, a problem arises when the subsidiary obligors suffer from catastrophic diseases, since they are in a situation of double vulnerability. The current regulations do not contemplate this legal problem, which produces an antinomy and violation of constitutional rights as a group of priority attention according to Article 35 of the Constitution of the Republic, highlighting also that there is the weighing of rights as established in Article 3 of the Organic Law of Jurisdictional Guarantees and Constitutional Control, the principle of the Best Interest of the Child must be considered and protected as the rights that people with serious health problems have. The State must ensure that the rights of both the subsidiary obligors in case of suffering from catastrophic or highly complex diseases and those of the fed are not violated, protecting the physical and psychological integrity, the right to health and food of both parties to ensure a good quality of life.